Development Of The Idea Of Criminal Individualization Of The Development Of Female Inmates - Suriyadi; Rayhani; Candra Kusuma Negara (LEGAL BRIEF, 2022)
The purpose of this study is to find out how to regulate the idea of criminal individualization in laws and regulations and analyze its implementation in the development of female prisoners in prisons, as well as the development of the concept of criminal individualization in the future. Research is carried out in descriptive analytics with normative and sociological juridical approaches to examine the abovementioned points. Data collection is carried out through field research and documentary research. Data analysis is carried out qualitatively. The results showed that the development of female prisoners based on criminal individualization had not been fully implemented as stipulated in Article 12 of Law No. 12 of 1995 concerning correctional services. This is due to the minimal capacity of the jail, the lack of facilities and infrastructure, and the lack of human resources. For this reason, in the future, it is necessary to develop the idea of criminal individualization in the development of female prisoners in the form of prison buildings increased and adjusted to the capacity of prisoners, methods and conditions or programs of coaching that are following the learning needs of prisoners, improving the quantity and quality of prison officers, the role of the community and private parties in the development of prisoners and the existence of open prisons. It is hoped that the Ministry of Law and Human Rights policy will add qualified prison officers under the required fields. In addition, it is necessary to build women's jails in each province, and there needs to be cooperation between the government and the private sector in developing prisoners. It also requires volunteers to guide and train ex-convicts to live independently. Prisoners whose sentence is less than 1 (one) year can be placed in open prisons or work in government or private institutions. It is necessary to build special narcotics correctional institutions and rehabilitation centers